Pengaruh Total Quality Management dan Kinerja Karyawan terhadap Employability Skill di UPTD BLK Disnaker Kota Semarang - Fildzah Mahdiya Karimah; Hendra Dedi Kriswanto (Departement of Mathematics Education, 2023)
Employability skills are an important issue that must be considered more deeply in the world of work. It is related to TQM and employee performance in an organization. The purpose of this study was to determine the effect of TQM and employee performance on employability skills at UPTD BLK Disnaker Semarang City. The target of this research is graduates of training participants at UPTD BLK Disnaker Semarang City. This study used a quantitative research method with an ex post facto research approach by distributing questionnaires. The data that has been obtained is then analyzed with multiple linear regression analysis. This study resulted in the finding that TQM and employee performance have a positive influence on employability skills. The implementation of the training process is accompanied by the application of TQM and good employee performance from the UPTD BLK Disnaker City of Semarang, so the employability skills of graduates of the training program will also increase. The importance of the contribution of all parties involved in the training process is able to encourage increased employability skills of the trainees. The benefits of research for the development of knowledge are adding references to empirical evidence regarding studies and discussions regarding the influence of TQM and employee performance on employability skills.